A typology of agency in new generation learning environments: emerging relational, ecological and new material considerations. (2nd January 2018) - Charteris, Jennifer; Smardon, Dianne
Abstract: The impetus to move to a new generation learning environments places a spotlight on the relational dynamics of classroom spaces. A key feature is the notion of learner agency. A complex notion, learner agency involves both compliance with and resistance to classroom norms and therefore is far more sophisticated than acting in acquiescence to expectations. This article traces a taxonomy of agency in education settings. The taxonomy details: sovereign agency of self-determination theory, relational agency linked with sociocultural theory, ecological agency -a temporally embedded process of social engagement, and emerging new material agency. Although the latter is starting to gain traction in Education research, it is yet to be explicitly recognised as an important consideration for educational practice. Consideration is given to this typology in light of case study data from school leaders who comment on learner agency in the context of new generation learning environments.